Productivity Measurement of Urea Fertilizer Production at PT. X Using The Green Productivity Approach - Rudi Saputra; Andrianto Indra Pratomo; Sumiyanto Sumiyanto (Greenation International Journal of Engineering Science, 2025)
Productivity is defined as a comparison between the output (Output) and input (Input) in the company which can also be said as the ratio between the amount of output produced and the number of inputs used. The purpose of this research is to measure the productivity and environmental performance of the urea fertilizer production process at PT. X by using the Green Productivity approach. Green Productivity is a method that can be used to increase the level of productivity as well as environmental performance. The first step is to identify the source of the waste from the field study, determine goals and targets, and choose alternative solutions for Green Productivity. Based on the Green Productivity methodology, the alternative solution is selected by calculating the EPI (Environment Performance Indicator) index, and the Green Productivity Index (GPI) for each alternative. From the results of the selection of these alternatives, the best solution that can be proposed for improvement is alternative 1, namely repairing and maintaining the hydrolyzer engine and making hydroelectric turbines. This result is obtained from the calculation of the material, labor, energy, and maintenance indexes which are above 1 which indicates a problem solving by selecting and implementing this alternative as a solution. The material GPI is 1.31, the human GPI is 1.05, the energy GPI is 1.11, the maintenance GPI is 1.01 and the waste GPI is 0.58. Meanwhile, the EPI index of human health is 16.67 and the EPI index of flora and fauna health is 15.23.